When Home Disappears: South Asia and the Growing Risk of Climate Conflict - Malji, Andrea (Terrorism and political violence, 2022)
This article highlights the multiple risks of political violence facing South Asia amid the backdrop of climate change. Specifically, it draws attention to Bangladesh and its shared border with Northeast India, a region with a long history of terrorism and insurgency. As the impact from climate change intensifies, there are several specific vulnerabilities in the region. First, internal migration within Bangladesh threatens to stress already weak infrastructures, especially in urban centers like Dhaka, which already hosts thousands of climate migrants. Internal rural-to-rural migration may further instigate clashes among farmers as they compete for diminishing agricultural resources. Second, cross-border migration from Bangladesh into India threatens to escalate existing tensions between Indians and Bangladeshi migrants, particularly in Northeast India. Violent identity movements within Northeast India are already common and a key grievance has been Bangladeshi presence in the region. These grievances have historically escalated into multiple separatist and terrorist organizations and threaten to escalate again. Hindu nationalist groups threaten to further exploit these existing tensions for political gain. Third, Rohingya refugee camps in Bangladesh are situated in a location that is at very high-risk for climate disasters. Cyclones and flooding threaten to create a new humanitarian crisis in the region. Finally, both Hindu and Islamic extremist groups may exploit grievances and utilize it for recruitment efforts. Together, these factors make South Asia particularly vulnerable to climate impacts. Using GIS, we map the climate vulnerable areas of Bangladesh alongside locations that have experienced fatal political violence from 2015–2020. We find that each administrative division faces its own unique challenges, but urban centers, areas near water, and border regions are the most vulnerable to climate conflict.